Evaluating the Acceptability, Swallowability, and Palatability of Film-Coated Mini-Tablet Formulation in Young Children: Results from an Open-Label, Single-Dose, Cross-Over Study - Juliane Münch; Isabelle Sessler; Hans Martin Bosse; Manfred Wargenau; Janine D. Dreesen; Giulio Loforese; Nicholas J. A. Webb; Rama Sivasubramanian; Sibylle Reidemeister; Philipp Lustenberger; Viviane Klingmann (MDPI AG, 2023)
Mini-tablets are advantageous over liquid formulations in overcoming challenges related to stability, taste, and dosage. This open-label, single-dose, cross-over study investigated the acceptability and safety of drug-free, film-coated mini-tablets in children aged 1 month-6 years (stratified: 4-6 years, 2-<4 years, 1-<2 years, 6-<12 months, and 1-<6 months), and their preference for swallowing either a high quantity of 2.0 mm or a low quantity of 2.5 mm diameter mini-tablets. The primary endpoint was acceptability derived from swallowability. The secondary endpoints were investigator-observed palatability, acceptability as a composite endpoint derived from both swallowability and palatability, and safety. Of 320 children randomized, 319 completed the study. Across all tablet sizes, quantities and age groups, acceptability rates based on swallowability were high (at least 87%). Palatability was rated as "pleasant/neutral" in 96.6% of children. The acceptability rates as per the composite endpoint were at least 77% and 86% for the 2.0 mm and 2.5 mm film-coated mini-tablets, respectively. No adverse events or deaths were reported. Recruitment in the 1-<6-months group was stopped early due to coughing-evaluated as "choked on" in three children. Both 2.0 mm and 2.5 mm film-coated mini-tablets are suitable formulations for young children.